2013
DOI: 10.1186/1742-2094-10-85
|View full text |Cite
|
Sign up to set email alerts
|

M-CSF increases proliferation and phagocytosis while modulating receptor and transcription factor expression in adult human microglia

Abstract: BackgroundMicroglia are the primary immune cells of the brain whose phenotype largely depends on their surrounding micro-environment. Microglia respond to a multitude of soluble molecules produced by a variety of brain cells. Macrophage colony-stimulating factor (M-CSF) is a cytokine found in the brain whose receptor is expressed by microglia. Previous studies suggest a critical role for M-CSF in brain development and normal functioning as well as in several disease processes involving neuroinflammation.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 69 publications
12
74
0
Order By: Relevance
“…Plasma levels of IL-6 are known to be elevated in HE patients (Shawcross et al 2007), however it is unclear whether circulating IL-6 can enter the brain in HE as the BBB remains largely intact (Rangroo Thrane et al 2012). Microglial proliferation can be stimulated in vitro by a number of cytokines such as M-CSF (Smith et al 2013), MCP-1 (Hinojosa et al 2011), GM-CSF and IL-3, however the addition of IL-6 to microglial cultures did not stimulate proliferation (Kloss et al 1997). It seems more likely therefore that IL-6 up-regulation in pHEs is a by-product of microglial activation rather than stimulating proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma levels of IL-6 are known to be elevated in HE patients (Shawcross et al 2007), however it is unclear whether circulating IL-6 can enter the brain in HE as the BBB remains largely intact (Rangroo Thrane et al 2012). Microglial proliferation can be stimulated in vitro by a number of cytokines such as M-CSF (Smith et al 2013), MCP-1 (Hinojosa et al 2011), GM-CSF and IL-3, however the addition of IL-6 to microglial cultures did not stimulate proliferation (Kloss et al 1997). It seems more likely therefore that IL-6 up-regulation in pHEs is a by-product of microglial activation rather than stimulating proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It seems more likely therefore that IL-6 up-regulation in pHEs is a by-product of microglial activation rather than stimulating proliferation. An important caveat here is that our exploration of proinflammatory cytokines was limited, excluding for example macrophage colony-stimulating factor (M-CSF) that was recently shown to stimulate proliferation in ex vivo human microglial cultures (Smith et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…C/EBPβ microglial expression is also upregulated by excitotoxic neuronal death in rat neuronalmicroglial co-cultures(Perez-Capote et al 2006). Recent studies in adult human microglial cultures have shown that C/EBPβ expression is upregulated by macrophage colony-stimulating factor, a microglial mitogen,(Smith et al 2013) and by the proinflammatory cytokines IL-1β, IL6 or TNFα(Strohmeyer et al 2014). The upregulation of microglial C/EBPβ and C/EBPδ upon pro-inflammatory stimulation has also been observed in experiments with the microglial cell lines BV2Ejarque-Ortiz et al 2010;Ejarque-Ortiz et al 2007a;Gresa-Arribas et al 2010;Jana et al 2003) and N9.…”
mentioning
confidence: 96%
“…MCSF has potent neuroprotective effects following auditory injury and in neuroinflammation (Smith et al, 2013;Yagihashi et al, 2005). We found that MCSF induces the expression of NRTN, which can explain at least in part the MCSF-induced formation of a neuronal network surrounding SMG tissue.…”
Section: Discussionmentioning
confidence: 80%